Environmental advertisement: An alternative policy to control consumption pollution - Eftichios Sophocles Sartzetakis; Anastasios P. Xepapadeas (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper examines the efficiency enhancing potential of supplementing existing policies of controlling consumption pollution with environmental advertisement. Our definition of environmental advertisement includes both information dissemination and persuasion. While incentive-based regulations that are based on coercion are effective immediately, environmental advertisement that is based on inducing voluntary action requires time. We formalise this argument by assuming that the shift of consumers' preference towards the desirable environmentally friendly goods or behaviour depends on the stock rather than the flow of advertisement. We assume homogeneous consumers, having the choice of consuming two goods one of which generates pollution. We treat environmental advertisement as a separate good within consumers' utility. Within a dynamic partial equilibrium framework, we analyse regulators' optimal control problem. We find that at the optimal steady state there is a positive stock of environmental advertisement. Thus, if we start with some small stock of advertisement, the stock increases monotonically while the rate of taxation decreases along the optimal path.
Keywords: D62; Q28; 330; Environmental advertisement; Pollution taxation; Dynamic optimisation; Second best optimum; Konsumtheorie; Umweltpolitik; Freizeitverhalten; Ökosteuer; Dynamische Optimierung; Policy-Mix; Second Best; Theorie